2014
DOI: 10.4161/15384047.2014.955764
|View full text |Cite
|
Sign up to set email alerts
|

Butyrylated starch affects colorectal cancer markers beneficially and dose-dependently in genotoxin-treated rats

Abstract: Abbreviations: AI, apoptotic index; AOM, azoxymethane; HAMS, high amylose maize starch; HAMSB butyrylated high amylose maize starch; HAMSB0, base diet containing 0% HAMSB; HAMSB5, base diet containing 5% HAMSB; HAMSB10, base diet containing 10% HAMSB; HAMSB20, base diet containing 20% HAMSB; HAMSB40, base diet containing 40% HAMSB; RS, resistant starch; SCFA, short chain fatty acid; SSB, single-stranded DNA breaksPopulation studies suggest that greater dietary fiber intake may lower colorectal cancer (CRC) ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…These studies suggest that butyrate produced by gut bacteria has a positive influence on gut health. Studies have indicated that butyrate obtained from natural dietary fiber can help maintain gut homeostasis and reduce the idiopathies of various diseases that develop due to dysbiosis (Toden et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…These studies suggest that butyrate produced by gut bacteria has a positive influence on gut health. Studies have indicated that butyrate obtained from natural dietary fiber can help maintain gut homeostasis and reduce the idiopathies of various diseases that develop due to dysbiosis (Toden et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Beneficial effects of other plant foods have been found, for example, black tea and wine extracts, but not green tea have shown to protect against AOMinduced colon carcinogenesis in rats (Caderni et al, 2000) and theaflavin-2, a major compound found in black tea extract was shown to induce apoptosis in human colon cell lines (Gosslau et al, 2011). Butyrate may reduce the risk of CRC in a dose dependent manner by enhancing apoptosis for damaged cells without promoting the risk of tumorigenesis through increased cell proliferation (Toden et al, 2014). In a study by Andersson et al, 2008(Andersson et al, 2008, ursolic acid, a pentacyclic triterpenoid also present in SO, was found to reduce the number of large ACF when given orally to rats during the initiation phase but not during the promotion/progression phase, results that are in agreement with our present study.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from animal trials and in vitro studies supports the anti-tumorigenic effects of butyrate. 24 , 29 , 46 In an animal model study conducted by Shen et al, 47 HDACi upregulated selective miRNAs to modulate B-cell differentiation and the immune response of the host. In vivo and in vitro studies found that butyrate can also modulate the inflammatory response by the suppression of nuclear factor κB activation.…”
Section: Butyrate and Risk Of Crcmentioning
confidence: 99%